2007
DOI: 10.1364/ao.46.008250
|View full text |Cite
|
Sign up to set email alerts
|

Resonant optical transmission from a one-dimensional relief metalized subwavelength grating

Abstract: We have studied one-dimensional (1D) relief metalized subwavelength gratings, which support resonant optical transmission. We have used pregrooved DVD stampers, metalized with a thin Al layer. The sensitivity of resonant transmission of the gratings to the cladding environment was investigated by the help of matching fluids. We have shown that the shift of the spectral position of the resonance peak can be used for sensor applications, e.g., for determination of very low concentrations of nanosized dielectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Grating-coupled SPR has been shown to produce enhanced optical transmission at specific wavelengths associated with a matching of the grating wavevector with that of SPPs at the metal/dielectric interface. , An example of this enhancement is shown in Figure , which depicts a series of p-polarized transmission spectra for light incident on a gold-coated grating as a function of angle of incidence. An enhanced transmission peak is evident at ∼750 nm for directly transmitted light (θ = 0°).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grating-coupled SPR has been shown to produce enhanced optical transmission at specific wavelengths associated with a matching of the grating wavevector with that of SPPs at the metal/dielectric interface. , An example of this enhancement is shown in Figure , which depicts a series of p-polarized transmission spectra for light incident on a gold-coated grating as a function of angle of incidence. An enhanced transmission peak is evident at ∼750 nm for directly transmitted light (θ = 0°).…”
Section: Resultsmentioning
confidence: 99%
“…We, and others, have previously demonstrated that enhanced transmission peaks associated with grating-coupled surface plasmon resonance can be used to quantify the thickness of adsorbed thin films or changing dielectric media. ,,, In order to investigate the impact of thin, coated films on the various transmission features observed in Figure , we constructed multilayer films of arachidic acid. Langmuir–Blodgett film deposition was used in order to controllably fabricate films of varying thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Normal incident light is mostly reflected by the metal grating, resulting in a narrow transmission band 20 . With the incident light illuminated on the periodic structure, diffraction occurs which formed the incident mode.…”
Section: Gmrf Designmentioning
confidence: 99%
“…Normal incident light is mostly reflected by the metal grating, resulting in a narrow transmission band. 20 With the incident light illuminated on the periodic structure, diffraction occurs which formed the incident mode. The inherent guided mode leaks out from the waveguide layer and interferes with the applied wave that results in a filtering response.…”
Section: Gmrf Designmentioning
confidence: 99%
“…We and others have previously demonstrated that a diffraction grating constructed from a commercial DVD supported SP-enhanced light transmission when coated with a thin metal film. , The observed enhanced transmission consists of narrow peaks in the visible spectrum, whose central wavelength can be tuned by simple rotation of the grating. In the work presented here, we describe a simple optical microscope-based method for monitoring the first-order diffracted peaks associated with enhanced transmission through a gold-coated diffraction grating.…”
mentioning
confidence: 91%